Hypoxia Generated by Avian Embryo Growth Induces the HIF-α Response and Critical Vascularization - Carroll, Christopher; Engström, Niklas; Nilsson, Patrik F.; Haxen, Emma R.; Mohlin, Sofie; Berg, Peter; Glud, Ronnie N.; Hammarlund, Emma U. (Frontiers in Ecology and Evolution, 2021)
Cancer research has transformed our view on cellular mechanisms for oxygen sensing. It has been documented that these mechanisms are important for maintaining animal tissues and life in environments where oxygen (O2) concentrations fluctuate. In adult animals, oxygen sensing is governed by the Hypoxia Inducible Factors (HIFs) that are stabilized at low oxygen concentrations (hypoxia). Cellular responses to hypoxia associates with cell immaturity (stemness) and proper tissue and organ development. During mammalian development, the initial uterine environment is hypoxic. However, during avian embryogenesis, O2 continuously equilibrates across the porous eggshell and the oxygenation status is more complex. Here, we investigate HIF dynamics and use microelectrodes to determine O2 concentrations within the egg and the embryo during the first four days of development. To determine the increased O2 consumption rates, we also obtain the O2 transport coefficient (DO2) of eggshell and associated inner and outer shell membranes, both directly (using microelectrodes in ovo for the first time) and indirectly (using water evaporation at 37.5°C for the first time). Our results demonstrate a distinct hypoxic phase (<5% O2) between day 1 and 2, concurring with the onset of HIF-α expression. This phase of hypoxia is demonstrably necessary for proper vascularization and survival. Our indirectly determined DO2 values are about 30% higher than those determined directly. A comparison with previously reported values indicates that this discrepancy may be real, reflecting that water vapor and O2 may be transported through the eggshell at different rates. Based on our obtained DO2 values, we demonstrate that increased O2 consumption of the growing embryo appears to generate the phase of hypoxia, which is also facilitated by the initially small gas cell and low membrane permeability. We infer that the phase of in ovo hypoxia facilitates correct avian development. The study highlights that insights from the cancer field pertaining to the importance of hypoxia can broadly inform our exploration of animal development and success.